The Influence of Gastronomic Experience on Consumer Loyalty Through the Mediation of Satisfaction and Image of Traditional Restaurants in Singkawang City, West Kalimantan - Nanda Nurjanah; Nining Yunianti; Moch. Nur Syamsu (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the mediation role of satisfaction and restaurant image on loyalty in traditional restaurants , Singkawang City, West Kalimantan. The primary objective of this research is to analyze the direct and indirect effects of gastronomic experiences on consumer loyalty through restaurant image and customer satisfaction . The research method used is quantitative , with data collection through a questionnaire distributed to 270 respondents selected using purposive sampling technique . The data was then analyzed using descriptive statistical analysis to provide an Overview of the respondent data and Partial Least Square – Structural Equation Modeling (PLS-SEM), processed using SmartPLS software . The results of the analysis show that gastronomic experience significantly and positively influences restaurant image with a t- statistic of 20.045 (> 1.96) and a p- value of 0.000 (<0.05). Gastronomic experience has a significant and positive effect on consumer satisfaction with a t- statistic of 19.864 (> 1.96) and a p- value of 0,000 (<0.05). Restaurant image has a significant and positive effect on consumer loyalty with a t- statistic of 3.581 (> 1.96) and a p- value of 0,000 (<0.05). Consumer satisfaction was also found to have a significant and positive effect on consumer loyalty with a t- statistic of 0.584 (> 1.96) and a p- value of 0.000 (<0.05). Furthermore , mediation analysis revealed that restaurant image significantly mediation the effect of gastronomic experience on consumer loyalty with t- statistics of 3.55 (> 1.96) and p- value of 0,000 (<0.05). Consumer satisfaction significantly mediation the effect of gastronomic experience on consumer loyalty with t- statistics of 11.08 (> 1.96) and p- value of 0.000 (<0.05), indicating complementary ( partial) mediation ). Overall , these findings confirm the acceptance of all hypothesis proposed in this study